2021
DOI: 10.1186/s12931-021-01747-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of capnography for prediction of obstruction severity in non-intubated COPD and asthma patients

Abstract: Background Capnography waveform contains essential information regarding physiological characteristics of the airway and thus indicative of the level of airway obstruction. Our aim was to develop a capnography-based, point-of-care tool that can estimate the level of obstruction in patients with asthma and COPD. Methods Two prospective observational studies conducted between September 2016 and May 2018 at Rabin Medical Center, Israel, included healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…After adjusting for potential confounders, we found that the parameters that could distinguish between mild/moderate and severe cases were vascular disorders, HDL, plasma fibrinogen, fructosamine, standard bicarbonate concentration, pCO 2 , age, eosinophil count, lymphocyte ratio, and apolipoprotein A1. The factors that could distinguish between mild/moderate and very severe cases were vascular disorders, HDL, plasma fibrinogen, fructosamine, pO 2 , plasma carbon dioxide concentration, standard bicarbonate concentration, pCO 2 , age, sex, allergic diseases, eosinophil count, lymphocyte (14,17). For instance, Chen et al developed a model for predicting disease severity in patients hospitalized for COPD exacerbation and found that neutrophil count percentage and demographic parameters were associated with a higher risk of COPD exacerbation; the area under the receiver operating characteristic curve was 0.84 (14).…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for potential confounders, we found that the parameters that could distinguish between mild/moderate and severe cases were vascular disorders, HDL, plasma fibrinogen, fructosamine, standard bicarbonate concentration, pCO 2 , age, eosinophil count, lymphocyte ratio, and apolipoprotein A1. The factors that could distinguish between mild/moderate and very severe cases were vascular disorders, HDL, plasma fibrinogen, fructosamine, pO 2 , plasma carbon dioxide concentration, standard bicarbonate concentration, pCO 2 , age, sex, allergic diseases, eosinophil count, lymphocyte (14,17). For instance, Chen et al developed a model for predicting disease severity in patients hospitalized for COPD exacerbation and found that neutrophil count percentage and demographic parameters were associated with a higher risk of COPD exacerbation; the area under the receiver operating characteristic curve was 0.84 (14).…”
Section: Discussionmentioning
confidence: 99%
“…These features included the following: α, β, γ, and δ angles (Fig. 2 ) [ 11 13 ]; gradients and residuals derived from fitting curves to phases, such as the expiratory plateau [ 14 ]; absolute and short-term variability of pCO 2 [ 15 ]; curvature and other higher-order time-based features such as the ratio of the expiratory to inspiratory phase [ 12 , 13 , 16 ]; and area under the curve (AUC), which is commonly calculated in volumetric capnography [ 16 , 17 ]. These features have a basis in the respiratory physiology literature, and in many cases have been hypothesized to relate to clinical airway obstruction.…”
Section: Methodsmentioning
confidence: 99%
“…As the number of breaths per capnogram varied, the median and standard deviation were calculated for the per-breath features in each capnogram. These features included the following: α, β, γ , and δ angles (Figure 2) [11, 12, 13]; gradients and residuals derived from fitting curves to phases, such as the expiratory plateau [14]; absolute and short-term variability of pCO 2 [15]; curvature and other higher-order time-based features such as the ratio of the expiratory to inspiratory phase [12, 13, 16]; and area under the curve (AUC), which is commonly calculated in volumetric capnography [16, 17]. These features have a basis in the respiratory physiology literature, and in many cases have been hypothesized to relate to clinical airway obstruction.…”
Section: Methodsmentioning
confidence: 99%